Investigating the T cell-specific role of Interleukin-4 receptor alpha (IL-4Rα) in tuberculosis (TB) - Rousseau, Robert Pierre (Department of Pathology, 2025)
Protective immunity to tuberculosis (TB) is dependent on the ability of the host to mount a robust T cell response. The main effector T cells which contribute to protection in TB include T helper (Th) Th1 and Th17 T cells. The Th2 response, associated with IL-4Rα mediated signalling, remains largely overlooked in TB. The role of IL-4Rα in TB appears to be different according to cell type. Deletion of IL-4Rα on macrophages has no effect on disease, but deletion of the receptor on B cells, leads to better control. This thesis aimed to explore the T cell-specific role of IL-4Rα in TB disease by making use of T cell specific knockout model, iLCKCreIL-4Rα-/lox. We found that absence of IL-4Rα on T cells results in a delay in the recruitment of T cells to the lung. This was demonstrated by decreased CD4 and CD8 T cell numbers during acute infection compared to littermate controls. Consequently, the bacilli are able to better establish infection and proliferate in the lung, shown by increases in lung mycobacterial burden at both acute and chronic stages of infection. However, no differences are observed in the spleen, indicating deletion of IL-4Rα does not have a role in the dissemination of TB. In the absence of IL-4Rα, T cells express higher amounts of T-bet or RORγt transcription factors, indicating stronger Th1 and Th17 responses, respectively. The stronger pro-inflammatory responses do not clear the pathogen, and instead contribute to immunopathology. During chronic infection, we observed higher amounts of IL-17 as well as a corresponding increase in neutrophils, which in turn lead to a decrease in alveolar free space. The promotion of increased Th1 CD4 T cells resulted in greater amounts of terminally differentiated (CD44+KLRG1+ ) which have a poor proliferative capacity despite secreting large amounts of IFN-γ. KLRG1 expression is also associated with a reduced ability to migrate into the lung parenchyma, the site of disease. We also found that these (CD44+KLRG1+ ) expressed reduced amounts of CXCR3, CD69, and CD103, which are all markers associated with poorer migration into the lung parenchyma. Importantly, these factors result in decreased survival in T cell-specific IL-4Rα mice. In conclusion this study demonstrates that absence of IL-4Rα on T cells promotes a predominant Th1/Th17 response, that results in delayed recruitment into the lung tissue, which ultimately proves detrimental for the host.